An Analysis Of Product Quality Control At Meubel Warsito Business In Jayakarta Village Of Central Bengkulu - Reni Suryani; Neri Susanti; Wagini Wagini (Penerbit Jurnal Indonesia, 2024)
The This study aims to determine product quality control at Meubel Warsito business in Jayakarta Village of Central Bengkulu. Based on the characteristics of the assessment obtained by the research sample, namely chair products from 1 to 15 September 2023 using the purposive sampling method. The type used in this research is quantitative analysis. The data collection method in this research is using interviews, observation, documentation and the analysis method is Statistical Quality Control (SQC) with calculations using Seven Tools. Based on the research results, it shows that the number of chair products examined was 200 production units with 47 production units producing defects and producing the highest proportion value, namely 50. The product defects obtained were still below the statistical control limit because the lower control limit (LCL) value was -2,435. The middle value (CL) is 0.235 with the upper control limit (UCL) value being 2.905. So that there is no increase in defective chair products, this research provides the implementation of product quality control so that the at Meubel Warsito business in Jayakarta Village of Central Bengkulu can improve the causes and effects of defective products.